Optimization of Copper-Ammonia-Sulfate Electrolyte for Maximizing Cu(I):Cu(II) Ratio Using pH and Copper Solubility - Zulqarnain Ahmad Ali; Joshua M. Werner (Waste)
An investigation has been carried out to understand the solution chemistry of the Cu-NH−-SO4−2 system, focusing on the effect of pH on the solubility of copper in the solution and maximizing the Cu(I):Cu(II) ratio. A Pourbaix diagram for the Cu-N-S system has also been created using the HSC Chemistry software for a wide range of Cu-NH3 species, unlike most other studies that focused only on Cu(NH3)42+ and Cu(NH3)52+ (Cu(II)) as the dominant species. The Pourbaix diagram demonstrated that the Cu(I) exists as Cu(NH3)2+, while the Cu(II) species are present in the system as Cu(NH3)42+ and Cu(NH3)52+, depending upon the Eh and pH of the solution. Copper precipitation was observed in the electrolyte at pH values less than 8.0, and the precipitation behavior increased as the pH became acidic. The highest Cu(I):Cu(II) ratio was observed at higher pH values of 10.05 due to the higher solubility of copper at higher alkaline pH. The maximum Cu(II) concentration can be achieved at 4.0 M NH4OH and 0.76 M (NH4)2SO4. In the case of low pH, the highest Cu(I):Cu(II) ratio obtained was 0.91 against the 4.0 M and 0.25 M concentrations of NH4OH and (NH4)2SO4, respectively. Meanwhile, at high pH, the maximum Cu(I):Cu(II) ratio was 15.11 against the 0.25 M (NH4)2SO4 and 4.0 M NH4OH. Furthermore, the low pH experiments showed the equilibrium constant (K) K < 1, and the high pH experiments demonstrated K > 1, which justified the lower and higher copper concentrations in the solution, respectively.